Madame Bovary et ses trente-quatre « vous », ou le retour du refoulé - Alain Vaillant (Flaubert: Revue Critique et Génétique)
Flaubert, as we all know, is the artist of impersonality, of the elocutionary disappearance of the novelist. And yet, in Madame Bovary, he intentionally introduces, thirty-four times, outside of any dialogue situation, a second person (you, yours, your…) that suggests the presence of a narrator addressing, beyond his characters, his readers – or even worse, strangely merging his readers with his characters. His readers, or more often his female readers: for the close analysis of these thirty-four occurrences proves not only that the recollection of romantic lyricism, even ironized, hovers over Flaubert’s writing, but that the author has a hard time dissimulating his male identity, then addressing his subtle analyst’s explanations to an audience of women: obviously impersonality has strict limits, those of genre (or gender).